2015
DOI: 10.1016/j.ajpath.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Increased Apoptosis, Altered Oxygen Signaling, and Antioxidant Defenses in First-Trimester Pregnancies with High-Resistance Uterine Artery Blood Flow

Abstract: The mechanisms of deficient placentation in the first trimester remain poorly understood, although apoptosis, hypoxia, and oxidative stress have been implicated. High uterine artery Doppler resistance indexes (RIs) are predictive of placental complications of pregnancy, such as preeclampsia, fetal growth restriction, and stillbirth. We provide evidence that even in the first trimester, pregnancies with high uterine artery Doppler RI demonstrate alterations in placental gene and protein expression. Apoptosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 66 publications
2
36
0
Order By: Relevance
“…However, more recent evidence has demonstrated that uterine artery Doppler waveforms better reflect maternal systemic vascular resistance rather than local uterine artery resistance (Kalafat et al 2018;Perry et al 2018c). The latter data would indicate that maternal uterine perfusion dictates the degree of placental invasion rather than the other way round -a hypothesis which is consistent with cellular and mechanistic studies of trophobalsat function (Leslie et al 2015;Wallace et al 2015;James-Allan et al 2018;Charolidi et al 2019).…”
Section: Preconceptional Subclinical Cardiovascular Dysfunction Predisupporting
confidence: 69%
See 1 more Smart Citation
“…However, more recent evidence has demonstrated that uterine artery Doppler waveforms better reflect maternal systemic vascular resistance rather than local uterine artery resistance (Kalafat et al 2018;Perry et al 2018c). The latter data would indicate that maternal uterine perfusion dictates the degree of placental invasion rather than the other way round -a hypothesis which is consistent with cellular and mechanistic studies of trophobalsat function (Leslie et al 2015;Wallace et al 2015;James-Allan et al 2018;Charolidi et al 2019).…”
Section: Preconceptional Subclinical Cardiovascular Dysfunction Predisupporting
confidence: 69%
“…The latter data would indicate that maternal uterine perfusion dictates the degree of placental invasion rather than the other way round – a hypothesis which is consistent with cellular and mechanistic studies of trophobalsat function (Leslie et al . ; Wallace et al . ; James‐Allan et al .…”
Section: Cardiorenal Interactions In the Pathophysiology Of Preeclampsiamentioning
confidence: 99%
“…For example, coronary artery occlusion causes myocardial damage – not the reverse. Our finding that abnormal first‐trimester uterine artery Doppler indices are invariably associated with defects in trophoblast oxygenation, cellular damage and function irrespective of pregnancy outcome, supports this hypothesis. Furthermore, we would like to point out that, in most cases of late‐onset pre‐eclampsia, mid‐trimester uterine artery Doppler indices are normal, becoming abnormal only in late pregnancy, just prior to development of pre‐eclampsia.…”
supporting
confidence: 74%
“…3 Interestingly, higher levels of apoptosis and altered antioxidant defenses have been observed in placentas from pregnancies with high-resistance uterine artery flow. 24 However, a quantitative systematic review of early clinical studies using likelihood ratio as a measure of diagnostic accuracy concluded that uterine artery Doppler flow velocity has limited diagnostic accuracy in predicting preeclampsia, fetal growth restriction, and perinatal death. 16 In a recent, large retrospective study (N=23,894 participants), uterine artery PI at 19 to 24 weeks gestation was associated with high detection rates for SGA neonates (<5 th percentile) at a ten percent false positive rate.…”
Section: Commentmentioning
confidence: 99%